1998
DOI: 10.1021/jm970709p
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of the Multidrug Resistance-Reversing Activity of d-Glucose Mimetics of Hapalosin

Abstract: When five substituents of hapalosin were placed on D-glucose, molecular modeling revealed that the substituents on mimetics 2 and 3 occupy similar spatial positions as the corresponding substituents on hapalosin. Mimetic 3 and all the glucopyranoside intermediates generated in its synthesis were assessed for their ability to reverse multidrug resistance (MDR) mediated by P-glycoprotein (P-gp) or the multidrug resistance-associated protein (MRP). None of the sugar compounds were as effective as hapalosin in inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Several syntheses for 80 and its respective analogs have been reported, with the purpose of obtaining compounds with similar or better MDR reversal activity. Some of the analogs did not fulfill this objective; for example, the glucose mimic of hapalosin (80) and 8-deoxyhapalosin, the triamide analogs, and N-demethylhapalosin 81 possessing a trans-amide, exhibited weak MDR reversal activity [180][181][182]. Through SAR studies, proline-containing congeners (82 and 83) were found to be more potent against MCF-7/ADR cells than 81 [182].…”
Section: Hapalosin and Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several syntheses for 80 and its respective analogs have been reported, with the purpose of obtaining compounds with similar or better MDR reversal activity. Some of the analogs did not fulfill this objective; for example, the glucose mimic of hapalosin (80) and 8-deoxyhapalosin, the triamide analogs, and N-demethylhapalosin 81 possessing a trans-amide, exhibited weak MDR reversal activity [180][181][182]. Through SAR studies, proline-containing congeners (82 and 83) were found to be more potent against MCF-7/ADR cells than 81 [182].…”
Section: Hapalosin and Derivativesmentioning
confidence: 99%
“…At 20 μM concentration, compound 80 significantly enhanced the accumulation of [ 3 H]-paclitaxel in SKVLB1 cells, and exhibited a similar activity to verapamil in breast cancer cell MCF-7/ADR in the range of 1.5-10 μM [180,181]. Several syntheses for 80 and its respective analogs have been reported, with the purpose of obtaining compounds with similar or better MDR reversal activity.…”
Section: Hapalosin and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugar amino acids have been classified as dipeptide isosteres by Kessler, showing that they can be considered as scaffolds for synthesis of type-I peptidomimetics also. In addition to the cases where saccharides have been investigated as somatostatin mimetics and HIV-protease inhibitors, they have been applied to the synthesis of cyclic endothelin antagonists, [16] thrombin inhibitors, [17] multidrug-resistant-associated protein inhibitor, [18] cytomegalovirus inhibitors, [19] integrin ligands, [20] fibrinogen receptor ligands, [21] LPA agonists and antagonists, [22] rhodopeptin mimetics, [23] cysteine protease calpain inhibitors [24] and inhibitors of the growth of human cell lines. [25] Synthesis of a β-Turn Mimetic Based on 1-Deoxymannojirimycin Somatostatin (SST) is a tetradecapeptide that regulates, through binding to its receptors (SSTR) a number of processes including the release of growth hormone and other pituitary hormones.…”
Section: Synthesis Of Non-peptide Peptidomimeticsmentioning
confidence: 99%
“…depsipeptide hapalosin 29 to target cancer [25]. Cancer chemotherapy treatments can provide temporary clinical improvement, but tumour cells that endure the initial therapeutic attack often recover with greater resistance to both the original and other structurally unrelated drugs.…”
Section: Synthesis Of Thrombin Inhibitors Based On 2-amino-2-deoxy-d-mentioning
confidence: 99%